2007
DOI: 10.1101/lm.408507
|View full text |Cite
|
Sign up to set email alerts
|

Selective attention is a primary determinant of the relationship between working memory and general learning ability in outbred mice

Abstract: A single factor (i.e., general intelligence) can account for much of an individuals' performance across a wide variety of cognitive tests. However, despite this factor's robustness, the underlying process is still a matter of debate. To address this question, we developed a novel battery of learning tasks to assess the general learning abilities (GLAs) of mice. Using this battery, we previously reported a strong relationship between GLA and a task designed to tax working memory capacity (i.e., resistance to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
68
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(83 citation statements)
references
References 23 publications
12
68
1
2
Order By: Relevance
“…In previous studies, secondary factors were occasionally observed, but were often difficult to interpret, suggesting that they were not extracting anything meaningful about the nature of the animals' cognition and were instead most likely due to chance. This is consistent with the relatively small amount of variance (typically less then 15%) accounted for by these factors (Matzel et al, 2003;Matzel et al, 2005;Kolata et al, 2005;Kolata et al, 2007).A subset of the animals reported here was also tested on two additional tasks (spatial win-stay and reinforced alternation) as well as the five tasks in the primary learning battery. It was hypothesized that these two tasks plus the spatial water maze would share a single domainspecific factor because of their common dependence on the hippocampus (O' Keefe & Speakman, 1987;Woods et al, 2000;Moser et al, 1995).…”
supporting
confidence: 81%
See 2 more Smart Citations
“…In previous studies, secondary factors were occasionally observed, but were often difficult to interpret, suggesting that they were not extracting anything meaningful about the nature of the animals' cognition and were instead most likely due to chance. This is consistent with the relatively small amount of variance (typically less then 15%) accounted for by these factors (Matzel et al, 2003;Matzel et al, 2005;Kolata et al, 2005;Kolata et al, 2007).A subset of the animals reported here was also tested on two additional tasks (spatial win-stay and reinforced alternation) as well as the five tasks in the primary learning battery. It was hypothesized that these two tasks plus the spatial water maze would share a single domainspecific factor because of their common dependence on the hippocampus (O' Keefe & Speakman, 1987;Woods et al, 2000;Moser et al, 1995).…”
supporting
confidence: 81%
“…Similarly, we reported finding a substantial positive correlation between the aggregate performance of mice in a battery of learning tasks and their ability to withstand competing demands on working memory (Kolata et al, 2005). Furthermore, we found that one aspect of working memory, selective attention, was most strongly predictive of general learning abilities (Kolata et al, 2007). Taken together, our previous work suggests a hierarchical structure of cognitive abilities in mice with domain general abilities, such as working memory, influencing domain specific abilities, such as spatial ability.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…To quantify individual differences in learning among mice, a variant of the procedures previously reported was used (Matzel et al 2003(Matzel et al , 2006Kolata et al 2005Kolata et al , 2007Kolata et al , 2008). All animals were tested in a series of six independent learning tasks (Lashley III Maze, passive avoidance, spatial water maze, odor discrimination, and fear conditioning) that place unique sensory, motor, motivational, and information processing demands on the animals.…”
Section: Behavioral Training and Testingmentioning
confidence: 99%
“…A subsequent study of correlations between WM abilities and g in mice attempted to determine the components of WM still further (43). It involved tests of WM retention time, WM retention capacity, as well as capacities for selective attention.…”
Section: Inability Tomentioning
confidence: 99%